2015
DOI: 10.1038/bjc.2015.174
|View full text |Cite
|
Sign up to set email alerts
|

Time-varying effect and long-term survival analysis in breast cancer patients treated with neoadjuvant chemotherapy

Abstract: Background:Recent studies have indicated the prognostic value of tumour subtype and pathological complete response (pCR) after neoadjuvant chemotherapy (NAC). However these results were reported after a short follow-up and using a standard Cox model which could be unsatisfactory for time-dependent factors. In the present study, we identified the prognostic factors for long-term outcome after NAC, considering that they could have an inconstant impact over time.Methods:Prognostic factors from 956 consecutive bre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
24
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 28 publications
2
24
0
Order By: Relevance
“…Time to recurrence has been shown to be an important prognostic factor in early breast cancer [8,9,18,3032], with patients with late recurrence having better outcomes than those with early recurrence [15]. However, the precise definition of “early” and “late” recurrence remains a matter of debate, with the threshold generally set at between two and five years [8,13,15,17,31,33].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Time to recurrence has been shown to be an important prognostic factor in early breast cancer [8,9,18,3032], with patients with late recurrence having better outcomes than those with early recurrence [15]. However, the precise definition of “early” and “late” recurrence remains a matter of debate, with the threshold generally set at between two and five years [8,13,15,17,31,33].…”
Section: Discussionmentioning
confidence: 99%
“…Some studies of adjuvant chemotherapy have reported better outcomes for patients with “late recurrences” than for those with “early recurrences”[1317]. However, only two studies have investigated the impact of time to local recurrence on distant metastasis-free survival in the neoadjuvant setting [9,18]. One limitation common to all these studies is that the threshold for distinguishing between early and late recurrences is chosen by the author and often defined arbitrarily as the median time to recurrence, a time point that does not necessarily separate subgroups with good and poor prognoses.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, we cannot ensure whether certain data were missing due to actual failure to perform the corresponding test, or space limitations in the article. [ 33 ] The authors might feel that it was unnecessary to perform these tests or had good reasons to make exemptions. [ 34 ] Finally, a comparison study between Chinese and non-Chinese journals may be necessary to decide whether this is a global issue.…”
Section: Discussionmentioning
confidence: 99%
“…Surgery [14,15,25,29,36] and CA 15-3 marker [15] are the other factors that can be considered in the survival analysis. Furthermore, the combination of the following factors have been suggested across different studies: familial history [24], smoking [24], affected side [20,39], place of residence [29], number of involved lymph nodes [22,24,27,31,34,35,37], stage [5,6,8,17,25,26,42], stage of surgery [25], tumor size [16, 19, 20-24, 27, 28, 31, 34, 35, 37, 38, 41], complete clinical and pathological response [41], medicine [29], type of pathology [32], type of treatment [17,21], chemotherapy [25,33,36,37], neoadjuvant chemotherapy [18], radiotherapy [25,33,36], number of metastasis [30], bone pain [30], and time interval leading to bone metastasis [42]. No study has considered chronic diseases as an effective factor of survival analysis.…”
mentioning
confidence: 99%